2005
DOI: 10.1124/jpet.105.092403
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Characterization of Agonists at δ-Containing GABAAReceptors: Functional Selectivity for Extrasynaptic Receptors Is Dependent on the Absence of γ2

Abstract: Several groups have characterized the pharmacology of ␣ 4 -or ␣ 6 ␤ 3 ␦-containing GABA A receptors expressed in different cell systems. We have previously demonstrated that the pharmacological profiles of a series of GABA A receptor agonists are highly dependent on the ␣ subunit and little on the ␤ and ␥ subunits, so to further understand the contribution of the different subunits in the GABA A receptor complex, we characterized a series of full agonists, partial agonists, and antagonists at ␣ 4 ␤ 3 , ␣ 4 ␤ 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
175
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(190 citation statements)
references
References 34 publications
14
175
1
Order By: Relevance
“…Experiments expressing human cRNAs in oocytes yielded similar results with respect to ethanol modulation of α 4 β 3 δ GABA A -Rs; the human subunits presented a pharmacological profile consistent with the literature, explored in more detail in a companion paper (Stórustovu and Ebert, 2006). The L(tk -) cell line stably expressing human α 4 β 3 δ and α 4 β 3 γ 2S showed lower overall sensitivity to ethanol potentiation, but again no differences between α 4 β 3 δ and α 4 β 3 γ 2S GABA A -Rs.…”
Section: Lack Of Sensitivity To Low Concentrations Of Ethanolsupporting
confidence: 60%
See 1 more Smart Citation
“…Experiments expressing human cRNAs in oocytes yielded similar results with respect to ethanol modulation of α 4 β 3 δ GABA A -Rs; the human subunits presented a pharmacological profile consistent with the literature, explored in more detail in a companion paper (Stórustovu and Ebert, 2006). The L(tk -) cell line stably expressing human α 4 β 3 δ and α 4 β 3 γ 2S showed lower overall sensitivity to ethanol potentiation, but again no differences between α 4 β 3 δ and α 4 β 3 γ 2S GABA A -Rs.…”
Section: Lack Of Sensitivity To Low Concentrations Of Ethanolsupporting
confidence: 60%
“…Several neuroactive steroids (5α-pregnane-3α-ol-20-one, alphaxalone, and 5α-pregnane-3α,21-diol-20-one or THDOC) were more potent modulators of GABA in α 4 β 3 δ than in α 4 β 3 γ 2 GABA A -Rs. More recent studies of human and rat α 4 β 3 δ expressed in oocytes replicated many of these findings (Borghese et al, 2006;Stórustovu and Ebert, 2006).…”
Section: Expression In Heterologous Systemssupporting
confidence: 56%
“…We first searched for slightly sedative doses of GAN after acute injections to locate the closest match to our previous study with THIP (Vashchinkina et al, 2012) that has a full agonistic profile at extrasynaptic GABA A receptors (Storustovu and Ebert, 2006). We found that GAN 30 mg/ kg produced a transient reduction in locomotor activity of young mice, whereas a 10 mg/kg dose did not affect activity (Figure 1a and b).…”
Section: Effects Of Gan On Locomotor Activity Of Micementioning
confidence: 99%
“…Thereafter, body temperature was recorded at different intervals (ranging from 15 to 30 min) after an i.p. injection of vehicle, GAN (30 mg/kg), or 4,5,6,7-tetrahydroisoxazolol[4,5-c]pyridine-3-ol (THIP, gaboxadol; 6 mg/ kg), a selective GABA-site agonist with a full agonist profile at d-subunit-containing GABA A receptors (Storustovu and Ebert, 2006). THIP has shown to induce neuroplasticity in VTA DA neurons but no reward-like behavior in CPP test in mice (Vashchinkina et al, 2012).…”
Section: Behavioral Experimentsmentioning
confidence: 99%
“…Indeed, immunogold studies suggest a limited expression the ␣4 subunit within synaptic regions of dentate granule cells (Sun et al, 2007;Zhang et al, 2007). However, in the thalamus, both functional studies demonstrating inhibitory actions for Ro154513 (a partial benzodiazepine "agonist" with positive allosteric activity at ␣4␤x␥2 receptors and negative modulatory activity at equivalent receptors incorporating ␣1-3 or ␣5 subunits) (Wafford et al, 1996) and immunohistochemical evidence highlighting an apparent lack of colocalization between ␣4-containing receptors and synaptic markers Kralic et al, 2006;Peden et al, 2008) argue against such an interpretation.…”
Section: Figure 6 Summation Of Ipscs During a Simulated Tonic Train mentioning
confidence: 99%